Combination of permanent hydrosilylation and reversible Diels–Alder reactions for self-healing poly(dimethylsiloxane) materials with enhanced ageing properties. (June 2022) - Yilmaz, D.; Lansade, D.; Lewandowski, S.; Perraud, S.; Llevot, A.; Carlotti, S.
Abstract: Poly (dimethylsiloxane)s (PDMS) are widely used in space applications thanks to their transparency, thermal and UV resistance, inter alia . The prolonged exposure of these materials to the geostationary environment leads to the apparition of cracks and changes in their optical properties, this being detrimental to their function. To enhance their lifespan, self-healing PDMS based on a dual network featuring both permanent and reversible units thanks to hydrosilylation and Diels–Alder reactions were designed. The tunable chemical composition of the networks was characterized by proton Nuclear Magnetic Resonance spectroscopy ( 1 H NMR) and Fourier-transformed infrared-attenuated total reflection (FTIR-ATR) measurements. The thermal and mechanical behaviors of pristine and healed materials were mainly studied by differential scanning calorimetry, dynamic mechanical analysis, and tensiometry. Ageing under proton irradiations was also performed, simulating part of the radiations encountered in geostationary environment. Ultraviolet-visible-near infrared analyses were carried out to compare the materials optical properties both before and after irradiations. Finally, chemical degradation mechanisms were studied by FTIR-ATR analyses and discussed. Graphical abstract: Image 1 Highlights: PDMS bearing both allyl and furan moieties with tunable composition were synthesized. Self-healing PDMS were elaborated by combining permanent hydrosilylation and reversible Diels–Alder chemistries. Addition of a permanent network maintained the initial PDMS mechanical properties even when Diels–Alder network broke. PDMS double networks led to enhanced ageing properties under proton irradiation.